(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
The historic city centers in Iraq boast numerous traditional buildings of great architectural importance, characterized by unique design features and elements from previous historical periods. However, they suffer from neglect and loss due to a lack of proper preservation strategies. Effectively preserving traditional buildings requires strategies firmly rooted in the customs and cultures of the areas to which they belong. Considering the sensitivity of these buildings, any incorrect decision in identifying appropriate conservation strategies can have a rapid and negative impact. Thus, in this study, the primary indicators for creating effective strategies for maintaining traditional buildings in Iraq’s historic city centers were determined. As a subject of a case study, a collection of historic buildings in Hillah’s historic city center was chosen. For the purpose of assessing the percentages of fulfilling the indications in the research samples using a five-point Likert scale, a questionnaire form was created and sent to fifty architecture specialists. After that, analysis was done using the statistical software (SPSS). Accordingly, the findings revealed a discrepancy in the percentages of research samples that met the indicators; the (benefit) indicator was given the highest evaluation, while the (preservation works) indicator was given the lowest. This calls for specialists and decision-makers to step in and develop suitable solutions.